Useful software tools to support the multidisciplinary design project - Lee, Shei Pin (2016)
With the evolving requirements of the Multidisciplinary Design Project course, the robotic systems of students are bound to get more complex. Therefore, more tools can be provided for students to aid them in building the systems which enable them to concentrate on their task domain and reducing the unrelated technical issues that they need to handle. For this project, a new suite of software tools were developed for the students who will take the MDP course, namely a fastest path calculator application and two applications to aid students in debugging their Android module, one for Windows PC and another for Android. The existing tool to debug the Android module is basic, rigid, unintuitive in some aspects and lacking in functions. The new Android Module Debugger application developed for this project, which will be replacing the existing tool hopes to solve these problems by providing better customization features and more useful debugging features, so that students can seamlessly integrate their mobile module with their Raspberry Pi module. Various usability and user experience design considerations were also implemented for the new application. The Fastest Path Calculator application for this project uses an implementation of the A* algorithm to solve for the fastest path in a given arena. The application uses the real-world specifications of the student’s robot as parameters to calculate the path cost and heuristics of the algorithm. Finally, a user study was conducted to understand the usability and user acceptance of the Android Module Debugger on PC.